Structural Changes in Cooked Rice Treated with Cooling-Reheating Process and Coconut Milk Addition as Observed With FT-IR and 13C NMR - Nuri Arum Anugrahati; Yudi Pranoto; Yustinus Marsono; Djagal Wiseso Marseno (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The molecular structural changes of food could be observed by the technique of FT-IR and 13C NMR spectroscopy. This research was aimed to study the structural changes in cooked rice treated with cooling-reheating process and coconut milk addition using FT-IR and 13C NMR. It was found that the cooling-reheating process and addition of coconut milk cause several structural changes of cooked rice. The IR analysis showed the bands at 3,400, 2,900, 1,018 and 856 cm-1 changed due to the retrogradation during cooling process. The spectrum of 13C NMR showed the change of peaks at 100.28 and 100.10 ppm. These changes may be related to the addition of coconut milk during rice cooking.